(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2025)
The contamination of ecosystems by heavy metals poses a substantial environmental and health hazard, primarily because Ions of metals such as copper (Cu²⁺), nickel (Ni²⁺), and zinc (Zn²⁺) are very poisonous, do not break down naturally, and bioaccumulate in living things. In this study, Cu²⁺, Ni²⁺, and Zn²⁺ ions are removed from water using polymer inclusion membranes (PIMs). Three distinct carriers, Ia, Ib, and Ic, together with a commercially available carrier named Aliquat 336, are evaluated for their transport efficiency. The PIMs were made using polyvinyl chloride (PVC) as the main polymer., and 2-NPOE was used as the plasticizer at the same time. SEM, or scanning electron microscopy, was used to analyze the membranes, and the results showed that there were changes in the surface morphology. The results of the transport studies demonstrated that the metal ion flow increased as the concentration of the carrier grew. Aliquat 336 maintained a better efficiency than the synthetic carriers throughout the trials. Cu2+ ions had the greatest transit rate among the metal ions that were investigated, followed by zinc ions and nickel ions. It has been shown via the findings that Aliquat 336 has greater complexation and membrane compatibility, which makes it a more efficient carrier in order to isolate ions of heavy metals by use of membranes.